Air-stable lithium metal anode with sputtered aluminum coating layer for improved performance. (10th September 2019) - Qu, Siji; Jia, Weishang; Wang, Ying; Li, Chao; Yao, Zeyu; Li, Kunyan; Liu, Yuchi; Zou, Wei; Zhou, Fu; Wang, Zhihong; Li, Jingze
Abstract: Li metal is considered as the preferred anode material to replace graphite in next generation of Li metal battery. However, the shortages including Li dendrite growth are hindering its practical application. In addition, Li metal is unstable in ambient air, which brings safety risk for assembling and operating of Li metal battery. Herein, we deposit Al thin film on Li foil as the protective layer by magnetron sputtering. The Al-coated Li metal electrode shows higher stability in the air and carbonate-based electrolyte. Moreover, the Li electrode with Al coating layer exhibits metallic luster even after 200 cycles, and the cycling lifetime is expanded over 950 h at 0.5 mA cm −2 and 0.5 mAh cm −2 . The improved electrochemical performance is attributed to the formation of a stable Li-Al alloy layer on the electrode surface, where the reduced Li atoms can diffuse into the alloy layer resulting in the formation of dense and compact Li metal anode.